Isu Global Manajemen Mutu dan Kualitas Total Pendidikan Studi Pada Universitas Islam Indonesia “UII” Yogyakarta - Mashuri, Mashuri; Latif, Mukhtar; Anwar, Kasful (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to understand the efforts made by Universitas Islam Indonesia in improving the quality of its education, as well as to get an overview of how total quality management is implemented at Universitas Islam Indonesia. Through this analytical qualitative approach, it is expected to reveal a picture of the quality, reality, and effectiveness of the Islamic University of Indonesia's educational institutions, especially in terms of its performance management. The results of total quality management at the Islamic University of Indonesia educational institution can show a significant positive impact on the institution, as well as for Muslims, especially in Indonesia and in general for Muslims around the world. There is a convincing correspondence between the data that the author obtained from observations and the results of interviews with the school, so it is known that the Islamic University of Indonesia Palembang has a quality appearance. This school has carried out a total management process or Total Quality Management (TQM) at every level of management, starting from determining the school quality policy by the top leadership, interpreting and implementing the policy into operational procedures at the middle management level, and carrying out technical work by the lowest line management and carrying out quality control with ISO 9001: 2008 standards very well.